Analisis Kinerja Rentabilitas Dan Solvabilitas Sektor Kosmetik Dan Rumah Tangga (Studi Kasus Perusahaan Yang Terdaftar Di Bursa Efek Indonesia) - Ima Halimah; Nor Norisanti; Faizal Mulia Z (Jurnal Samudra Ekonomi dan Bisnis, 2019)
This study discusses the analysis of capital structures that measure profitability and solvability in cosmetic companies listed on the Indonesia Stock Exchange. This research uses descriptive method, the data used secondary data consisting of financial statements of cosmetics companies for the period 2015 to 2017. Using horizontal analysis for capital structure, return on equity (ROE), debt to equity ratio (DER), long term debt to equity ratio (LTDtER) and uses industry standard averages. The results show that PT Unilever Indonesia Tbk can exceed the average value of the industry standard and the value generated for returns on equity, debt to equity ratio, and long-term debt to equity ratio the higher compared to other cosmetic companies. Companies with returns on equity, debt to equity ratios and long-term debt-to-equity ratios that obtain low scores are PT. Kino Indonesia Tbk and PT. Mustika Ratu Tbk because the value obtained cannot always be obtained by the industry standard average value. Keyword : Capital Structure, Returns On Equity, Debt To Equity Ratios, Long Term Debt To Equity Ratios